"And He Could Wear a Dress?": A Preschool Transformative Book Conversation. (17th July 2018) - Quast, Erin
Abstract: How might literature be shared with students for transformative purposes? Literature has the power to shape students' worldviews through the exploration of diverse human experiences, but how students engage with diverse characters is important to reaching transformative goals. The author identified teachers' pedagogical moves within a preschool conversation on gender around the picture book My Princess Boy by Cheryl Kilodavis. Noticing how gender normativity manifested in the classroom, teachers used the book to open the conversation on gender, honor students' sensemaking, and complicate gender norms through responsive listening. Using examples of teacher–student interactions across the preschool book conversation, practical suggestions are provided for teachers to facilitate transformative dialogue when sharing diverse texts with young students.